Influence of local shunting on the electrical performance in industrial Silicon solar cells. (1st December 2016) - Somasundaran, P.; Gupta, R.
Highlights: Quantification of shunt related losses considering critical shunt locations and finger proximity. Identification of critical shunt locations in industrial Silicon solar cells and influence of fingers. 90–95% difference in relative power found between different shunt locations at 1000 W/m 2 irradiance . 80% difference in relative power found between different shunt locations at 100 W/m 2 irradiance . 70% difference in relative open circuit voltage found between different shunt locations at low irradiances . Abstract: The paper presents the results of investigation on the influence of an ohmic shunt located at various spatial positions on the solar cell performance by distributed diode model based simulations. By systematically varying the parameters such as shunt resistance, proximity to metallization, shunt area, and irradiance a deep insight about the shunt impact on the solar cell performance have been obtained. Further, effect of spatial positioning of shunts has been investigated by considering shunted region of same area and severity at various locations of the solar cell, via the simulation approach. The presented simulation approach has been experimentally validated. The influence of shunt on the relative power and relative open circuit voltage has been studied considering different irradiance levels. The study revealed new insights about significance of spatial positions of the shunts and the proximity of finger and busbar metallization. A dramatic improvement in the solar cell's electrical performance can be gained by either preventing the occurrence of shunts at the identified critical locations or isolating them by laser or chemical technique or removing them.